2017
DOI: 10.1007/s00217-017-2953-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre-treatment and drying method on physico-chemical properties and dry fractionation behaviour of mealworm larvae (Tenebrio molitor L.)

Abstract: protein (52.5-58.2%db) and fat (21.4-26.6%db) content. Highest protein recovery of max 72% was determined in the particle size fraction 500-1000 µm. Concluding, these results provide insights into physico-chemical characteristics of mealworms affected by pre-treatment and drying. The potential of dry fractionation techniques for protein enrichment and delivery of a variety of differently composed mealworm fractions was demonstrated and may provide an interesting potential to optimize water and energy consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 51 publications
(73 reference statements)
4
70
0
2
Order By: Relevance
“…The extracted fractions were slightly more yellow compared to the LM. The brown and yellow colour could be due to lipophilic melanoidins, which during defatting and consequent protein extractions may be removed, creating higher a* and L* values [ 37 ]. This idea is consistent with other studies, that found a lighter defatted sample compared to whole and extracted fractions [ 15 , 16 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The extracted fractions were slightly more yellow compared to the LM. The brown and yellow colour could be due to lipophilic melanoidins, which during defatting and consequent protein extractions may be removed, creating higher a* and L* values [ 37 ]. This idea is consistent with other studies, that found a lighter defatted sample compared to whole and extracted fractions [ 15 , 16 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…A slight increase in moisture has been reported after blanching, (Azzollini, Derossi, & Severini, 2016;Purschke et al, 2018a). In T. molitor L., an increase in moisture was reported (from 62.81% to 70.44% after 40 s), but water activity (available water) remained constant (0.96) .…”
Section: Blanchingmentioning
confidence: 97%
“…The highest protein recovery was obtained with the particle size fraction 500 to 1000 µm. Fractionation is, therefore, a promising strategy for producing standardized insect‐based intermediates with a view to industrial applications and consumer acceptance (Purschke et al., ).…”
Section: Processing Technologiesmentioning
confidence: 99%
See 2 more Smart Citations